2012 IEEE International Geoscience and Remote Sensing Symposium 2012
DOI: 10.1109/igarss.2012.6352516
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of inter-sensor NDVI relationships based on analytical representation of soil isolines

Abstract: This study introduces an analytical approach to derive a relationship between values of Normalized Difference Vegetation Index (NDVI) obtained from datasets of two sensors with different band passes in the context of inter-sensor crosscalibration of such vegetation index (VI) products. Derivation of the relationship has been performed based on a concept of soil isolines. Starting from the soil isoline equations, an inter-sensor NDVI relationship was derived and represented by a system of equation with a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Our intention was to eliminate the influences of the spatial resolution, the viewing and illumination geometries, and so on, from the influences of the sampling wavelength. Similar approaches have been explored in our pilot studies [52][53][54][55].…”
Section: Derivation Steps For Obtaining the Intersensor VI Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our intention was to eliminate the influences of the spatial resolution, the viewing and illumination geometries, and so on, from the influences of the sampling wavelength. Similar approaches have been explored in our pilot studies [52][53][54][55].…”
Section: Derivation Steps For Obtaining the Intersensor VI Relationshipsmentioning
confidence: 99%
“…The use of the soil isoline for the intercalibration of VI data has been examined briefly in pilot studies [52][53][54][55], which indicated that the soil isoline equation may provide good insights into the intersensor spectral differences. This study attempts to further advance the derivation and numerical validation studies.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The work needs to be extended to cover different types of VIs such as Ratio VI (RVI), Different VI (DVI), Perpendicular VI (PVI), Soil Adjusted VI (SAVI), and two-band Enhanced VI (EVI2). Applicability of our previous work needs to be investigated, where this study try to address.…”
Section: Introductionmentioning
confidence: 99%